Den skickligt inkompetente chefen (Sociologisk Forskning, 2008)
The skilled incompetent managerBased on a critical interpretation of a leadership seminar we illustrate how the performance of the managers involved skilled incompetence. It expresses itself through a non-critical attitude, easily-made solutions and pseudo-communication, which together fuel a kind of knowledge flexibility. This uncritical, somewhat shallow and pragmatic attitude towards knowledge (e.g. management concepts), ought not to be understood as just dysfunctional, but also as a more or less unaware but adjusted competence, that in some situations works as a social lubricant in bureaucratic organizations.